2018
DOI: 10.1136/tobaccocontrol-2018-054266
|View full text |Cite
|
Sign up to set email alerts
|

Availability, price and promotions for cigarettes and non-cigarette tobacco products: an observational comparison of US Air Force bases with nearby tobacco retailers, 2016

Abstract: Retail stores located on Air Force bases sell cigarettes and smokeless tobacco products at prices well below those in nearby off-base retailers: the vast majority of these retailers feature interior price promotions for these products. Federal policies regulating prices of on-base tobacco sales, if implemented more effectively, have the potential to protect the health of Airmen by helping them remain tobacco-free after technical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…A census of on-base retailers was created using our previous 2016 work33 and by consulting AFB websites and staff who worked on each base. We then employed several strategies to identify all off-base retailers within the 1.5-mile road network service areas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A census of on-base retailers was created using our previous 2016 work33 and by consulting AFB websites and staff who worked on each base. We then employed several strategies to identify all off-base retailers within the 1.5-mile road network service areas.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, after the implementation of this DoD policy, phone surveys of tobacco retailers indicated that cigarette prices were 12.5%–24.5% cheaper on military bases compared with the most proximal Walmart store 25 31 32. In 2016, our team visited on-base and off-base DoD stores at Air Force Technical Training Bases in Texas and Mississippi and collected data on the prices of cigarettes and other tobacco products 33. We found that Marlboro Red and Newport Menthol packs were between $0.80 and 0.87 cheaper on base, which amounted to a $292–318 annual savings for an individual who smokes a pack a day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te rapid development of the tobacco industry has intensifed the market competition among various tobacco companies [1]. Tobacco product quality is one of the important ways for tobacco companies to improve their market competitiveness; tobacco companies need to secure the overall quality of tobacco to gain a competitive advantage in the market, and the quality of tobacco products produced on line is often measured by the roundness index of tobacco flter rods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Within the US Air Force, approximately 5.9% of Airmen trainees (called such regardless of sex or gender identity) report current use of cigarettes, 2.1% current use of smokeless tobacco, 2.2% current use of hookah, and 15.3% current use of ENDS 13 . These rates are likely driven by a long history of targeted tobacco advertising and promotion on military bases 14 , 15 , a culture that supports tobacco use 16 , and the availability of cheap tobacco products on the base 17 . Previous studies have documented that the training year is a particularly high-risk period for tobacco use, with 7.9% to 12.4% of never users initiating tobacco products for the first time during this time 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%